Biblical interpretation in early Christian Gospels: Volume 4: The gospel of John - Hatina, Thomas R. (Library of New Testament studies, 2020)
"This volume is the fourth in a set of volumes, which together explore current approaches to the study of scripture in the Gospels. Thomas R. Hatina's latest edited collection begins with an introduction surveying methodological approaches used in the study of how scriptural allusions, quotations, and references function in John, with subsequent essays grouped into four categories that represent the breadth of current interpretive interests. The contributors begin with historical-critical approaches, before moving to rhetorical and linguistic approaches, literary approaches, and finally social memory approaches. Each study contains not only recent research on the function of scripture in John, but also an explanation of the approach taken, making the collection an ideal resource for both scholars and students who are interested in the complexities of interpretation in John's context as well as our own."--